Effects of Early Empagliflozin Initiation on Diuresis and Kidney Function in Patients With Acute Decompensated Heart Failure (EMPAG-HF) - Schulze, P Christian; Bogoviku, Jürgen; Westphal, Julian; Aftanski, Pawel; Haertel, Franz; Grund, Sissy; von Haehling, Stephan; Schumacher, Ulrike; Möbius-Winkler, Sven; Busch, Martin (Circulation (New York, N.Y.), 2022)
Effective diuretic regimens using loop diuretics in patients with acute decompensated heart failure are often limited by the development of worsening kidney function. Sodium-glucose cotransporter-2 inhibitors induce glucosuria and sodium excretion with nephroprotective effects in patients with stable heart failure but their role in acute decompensated heart failure is unclear. In this single-center, prospective, double-blind, placebo-controlled, randomized study, we randomly assigned patients with acute decompensated heart failure to empagliflozin 25 mg daily or placebo in addition to standard decongestive treatments that included loop diuretics. The primary end point was cumulative urine output over 5 days. Secondary end points included diuretic efficiency, dynamics in markers of kidney function and injury, and NT-proBNP (N-terminal pro-B-type natriuretic peptide). Sixty patients were randomized within 12 hours of hospitalization for acute decompensated heart failure. Addition of empagliflozin daily to standard medical treatment of acute decompensated heart failure resulted in a 25% increase in cumulative urine output over 5 days (median 10.8 versus 8.7 L mL in placebo, group difference estimation 2.2 L [95% CI, 8.4 to 3.6]; =0.003). Empagliflozin increased diuretic efficiency compared with placebo (14.1 mL urine per milligram furosemide equivalent [95% CI, 0.6-27.7]; =0.041) without affecting markers of renal function (estimated glomerular filtration rate, 51±19 versus 54±17 mL/min per 1.73 m²; =0.599) or injury (total urinary protein, 492±845 versus 503±847 mg/g creatinine; =0.975; and urinary α1-microglobulin, 55.4±38.6 versus 31.3±33.6 mg/g creatinine; =0.066) with more pronounced decrease in NT-proBNP in the empagliflozin group compared with placebo (-1861 versus -727.2 pg/mL after 5 days; quotient in slope, 0.89 [95% CI, 0.83-0.95]; <0.001). There were no differences in the incidence of safety events between groups. Early addition of empagliflozin to standard diuretic therapy increases urine output without affecting renal function in patients with acute decompensated heart failure. URL: https://www. gov; Unique identifier: NCT04049045.